Perspectiva genética del tratamiento nutricional en la enfermedad cardiovascular (2013)
Introduction: the cardiovascular disease is multifactorial relationship processes including genetic factors and potentially modifiable risk factors, such as diet. The current nutritional recommendations focus on reducing modifiable risk factors, the highlighting the control of elevated plasma cholesterol eg. However, this variable is only within the multiple risk factors associated with cardiovascular disease. Objective: know to interactions related nutrigenétics nutrigenomics and cardiovascular disease. Methodology: systematic review of literature in the databases PubMed, and Sciel o ELSEIVER. Results: the nutritional interaction as some genes, hepatic lipase, apolipoprotein A1, A-4, A5 and apolipoprotein E modulate plasma lipid levels, this increases the risk of developing cardiovascular disease, without neglecting the effects of diet rich in saturated fatty acids. Although this shows that not all individuals respond equally to fat and not all develop the disease. This concept is applicable in the context of the personalized nutrition as prevention and treatment of cardiovascular diseases. Conclusions: the treatment of cardiovascular disease depends on the genetic variants that influence the response to diet and the way how certain nutrients influence the genome. (MÉD.UIS.2013;26(1):29-35)